A Concise Asymmetric Total Synthesis of (+)-8-Epigrosheimin via Catalyst-Free Tandem Allylboration–Lactonization - Maity, Dhananjoy; Maity, Ramkrishna; Jana, Manoranjan; Hajra, Saumen (Synlett, 2024)
A concise and scalable asymmetric synthesis of (+)-8-epigrosheimin is reported in nine steps using only three column chromatographic purifications with an overall yield 47.0% from (R)-(–)-carvone. Two synthetic routes are evaluated by catalyst-free tandem allylboration–lactonization of two carvone-derived aldehydes and subsequent ene cyclization, where strategy via Lee–Lay aldehyde is found to be more effective for 8-epigrosheimin.
Keywords: guaianolides; sesquiterpene lactone; tandem allylboration–lactonization; catalyst-free; ene reaction; 8-epigrosheimin